Die kerkorde van die Ned. Geref. Kerk: uitgangspunte ten opsigte van Skrif, belydenis en kerkorde - P. J. Strauss (Acta Theologica)
The Church Order of the Dutch Reformed Church puts the position of the Scriptures, its confessions of faith and its order for the church in a truly reformed perspective. In some instances this can be traced to the famous Synod of Dordt of 1618-1619. Supported by resolutions from the General Synod, these points of departure indicate the official stance of this church on these issues — a stance which can only be changed, be it officially, by changing the formulations in the Church Order. The Scriptures are regarded as the objective Word of God. With regard to the confessions, quia does not necessarily mean that one supports every reference or remark, but it indicates that the doctrine it confesses and formulates is according to the Scriptures. With regard to the offices, the assemblies and the relationships of the church, this Church Order differs from an attitude which has been accepted over many years by other reformed churches. Two dangers lie ahead for the Dutch Reformed Church. On the one hand, conservatism with a confessionalism that regards the confessions as canonical for all practical purposes. On the other hand, the church may endeavour to keep up with the times to such an extent that it exchanges Scriptures as a point of departure for humankind itself: It chooses to be liberal in the sense of an unrestricted freedom for humankind.